Safety of Levetiracetam in paediatrics: a systematic review - Egunsola, Oluwaseun; Choonara, Imti; Sammons, Helen (Public Library of Science, 2016)
Objective To identify adverse events (AEs) associated with Levetiracetam (LEV) in children. Methods Databases EMBASE (1974-February 2015) and Medline (1946-February 2015) were searched for articles in which paediatric patients (≤18 years) received LEV treatment for epilepsy. All studies with reports on safety were included. Studies involving adults, mixed age population (i.e. children and adults) in which the paediatric subpopulation was not sufficiently described, were excluded. A meta-analysis of the RCTs was carried out and association between the commonly reported AEs or treatment discontinuation and the type of regimen (polytherapy or monotherapy) was determined using Chi2 analysis. Results Sixty seven articles involving 3,174 paediatric patients were identified. A total of 1,913 AEs were reported across studies. The most common AEs were behavioural problems and somnolence, which accounted for 10.9% and 8.4% of all AEs in prospective studies. 21 prospective studies involving 1120 children stated the number of children experiencing AEs. 47% of these children experienced AEs. Significantly more children experienced AEs with polytherapy (64%) than monotherapy (22%) (p<0.001). Levetiracetam was discontinued in 4.5% of all children on polytherapy and 0.9% on monotherapy (p<0.001), the majority were due to behavioural problems. Conclusion Behavioural problems and somnolence were the most prevalent adverse events to LEV and the most common causes of treatment discontinuation. Children on polytherapy have a greater risk of adverse events than those receiving monotherapy.